Memento mori ca repetiție a finitudinii: Moartea, dincolo de Heidegger și Levinas - Turcan, Nicolae (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
Exemplified especially by Heidegger and Levinas, the phenomenology of death expresses first, the impossibility of the death experience, second, the authenticity of Dasein starting from the horizon opened by the possibility of death, and third, the relevance of the death of the other to the discovery of one’s own death. This article tries to take a step further, showing the link between the authenticity of Dasein and the desire for immortality manifested in this authenticity. By overturning Heidegger’s theses and by affirming both the necessity of an authentication of death itself - in accord with Socrates’s death example - and the legitimacy of the meditation on death, this text links the need for immortality, which is phenomenologically visible, with the Christian faith in the resurrection, which is visible only for theology.